White Paper on European Patient Needs and Suggestions on Chronic Type 2 Inflammation of Airways and Skin by EUFOREA - De Prins, Louise; Raap, Ulrike; Mueller, Tara; Schmid-Grendelmeier, Peter; Haase, Christiane H.; Backer, Vibeke; Fokkens, Wytske; Benoist, Linda B.; Prokopakis, Emmanuel; Doulaptsi, Maria; Hopkins, Claire; Claeys, Nele; et al. (Frontiers in Allergy, 2022)
Background: Type 2 inflammation underlies the chronicity of disease in subgroups of patients with asthma, chronic rhinosinusitis with nasal polyps (CRSwNP) and atopic dermatitis (AD), that often co- exist. Although several studies have investigated the unmet needs of asthma, AD and CRSwNP as such, little is known about the similarities and differences in experiences and perspectives of the current management of patients with comorbid Type 2 inflammatory diseases. Aims: To improve insight into the common and organ-specific needs of patients with Type 2 inflammation and comorbidities, allowing the formulation of recommendations to better address these needs in the future. Methodology: This qualitative study was conducted between July 2021 and December 2021 using semi-structured telephone interviews with patients suffering from year-long severe chronic Type 2 inflammation and at least one co-morbid inflammatory condition. Seven participating academic centers in Europe interviewed asthma (Copenhagen and Leuven), CRSwNP (London, Amsterdam and Crete) and/or AD (Oldenburg and Zurich) patients on patient characteristics, disease severity, shortcomings of current care pathways and suggestions for improvement of care. Transcripts were analysed using an inductive thematic analysis approach. Results: 81 patients with severe Type 2 inflammation and comorbidities were interviewed. Similar needs were recognised by patients with Type 2 inflammation, with both a lack of coordination in care and a lack of a real cure reported as being most frustrating. However, several needs are specific to asthma, CRSwNP and AD. Suggestions for improvement of care were generic across diseases, such as the implementation of a multidisciplinary approach, the improved facilitation of access to better treatments, the increase of general awareness on disease burden, and better educational programs for healthcare providers and patients. Of note, patients with CRSwNP also stated the need for alternatives to sinus surgery, whereas patients with asthma requested better medical care to prevent exacerbations and patients with AD would warmly welcome the reimbursement of emollients. Conclusion: Patients with asthma, CRSwNP and AD have shared unmet needs that need to be addressed by physicians, the academic community and health policy makers. This survey provides unique recommendations made by patients for the implementation of better care.